Revising Culture, Reinventing Peace: The Influence of Edward W. Said by Naseer Aruri and Muhammad Shuraydi, eds. (New York: Olive Branch Press, 2001. 190 pages.) (American Journal of Islam and Society, 2003)
In 1997, a group of scholars gathered at the University of Windsor to honorEdward W. Said and his lifetime achievements as a scholar and activist witha conference entitled “Culture, Politics, and Peace.” The present volume, a collection of the papers presented, show just how far reaching his influencehas been over the last three decades. While his profound influence on comparativeliterature and Palestine studies are well known, this volume revealshow his writings have prompted generations of scholars to question takenfor-granted postulations, discourses, and paradigms in literature, area studies,and politics. The papers also applaud his role as an advocate of thePalestinian cause and the way he has tirelessly and critically observed anddocumented the Palestinians’ fate.The three parts following Richard Falk’s introduction, “Nationalism,”“On Orientalism,” and “To Palestine,” address three dominant themes inSaid’s works. In “Empowering Inquiry: Our Debt to Edward W. Said,” Falkcelebrates Said’s work as a scholar of many interests and talents, and outlineshow his deeply humanist worldview, personal experience as an exile,and critical mind have produced the impressive oeuvre of a leading intellectualof our time. Falk is also the first to mention Said’s emphasis on secularismand his constant critique and warning against bringing religion intothe realm of knowledge and politics. This has not prevented Said fromdefending religious freedom and Muslims in particular, but might have ledhim to underestimate the moral and intellectual appeal of religious traditionsand a religious approach to knowledge. In the case of Palestine andPalestinian politics, his uncompromisingly secular and anti-sectarian viewsat times make his visions for the future seem incompatible with the region’srealities. Falk points out that Said’s rejection of religion relates to his rejectionof absolute truths, or the claim to it, and that he instead chose a “compassionateand engaged rationalism” as his worldview.The section on “Nationalities” starts with Lennard J. Davis’ fascinatingessay on “Nationality, Disability, and Deafness,” in which he convincinglyargues for the status of deaf people as a nation or community with nation-likefeatures. He explains his work with disability as influenced by Said’s workand engagement in political activism. Davis recalls his personal encounterswith Said as a teacher and scholar, and relates his own engagement in advocacyfor the deaf to Said’s influence ...